Effective mnemonic techniques for memorizing the peripheral nervous system: a focus on the brachial, lumbar, and sacral plexuses - Tianjun, Zhai; Honglei, Quan; Yeping, Chen; Wei, Feng (Frontiers in Surgery, 2025)
Background and aimsThe complex anatomy of peripheral nerve plexuses, such as the brachial, lumbar, and sacral plexuses, poses significant challenges in medical education. Traditional educational methods often prove inadequate in facilitating the retention of detailed information about these nerve structures. This study aims to propose innovative mnemonic techniques to enhance memory retention and simplify the learning process for medical students and professionals.MethodsWe developed and implemented various mnemonic techniques, including diagrams, rhyming mnemonics, and sequential methods, to facilitate the memorization of the peripheral nerve plexuses.InterpretationThe use of mnemonic techniques, including visual aids and structured learning strategies, can address the educational challenges posed by the intricate anatomy of peripheral nerve plexuses. These methods not only expedite the memorization of nerve branches but also elucidate their origins, enhancing diagnostic precision and therapeutic outcomes in clinical settings.